Decontamination of Ni(II) and Co(II) ions from Aqueous Medium using the Cola Lepidota Pericarp - Oladimeji, Adesanmi Segun; Uzoamaka, Ibezim Ezeani Millicent; Chidi, Obi (UI Scholars Hub, 2019)
In this study, the batch adsorption of Ni(II) and Co(II) ions was investigated by using the pericarp of Cola lepidota as the adsorbent. The pulverized sample was modified using sodium hydroxide. In addition, the effects of pH, particle size, contact time, temperature, and initial concentration on adsorption were investigated. Results revealed that maximum adsorption of metal ions are observed at pH of 6, a contact time of 60 min, and a temperature of 70 ºC. In addition, modification was to considerably impact the effectiveness of the adsorbent. The percentage removal of the metal ions on the modified (MCLR) and unmodified adsorbents (UCLR) followed increasing order of Co(II) ion on UCLR < Ni(II) ion on UCLR < Co(II) ion on the NaOH-modified adsorbent < Ni(II) ion on the NaOH-modified adsorbent. Equilibrium data were analyzed by the Langmuir and Freundlich isotherm models, and kinetic studies were carried out using pseudo-first-order and pseudo-second-order models. The adsorption data were well fitted to the Freundlich isotherm model equation, with correlation coefficient (R2) values greater than 0.950, and the pseudo-second-order kinetic model, with correlation coefficient (R2) values greater than 0.990. The monolayer adsorption capacities for modified C. lepidota residue and unmodified C. lepidota residue were 5.890 mg/g and 5.627 mg/g, respectively.